Training in Making and Utilizing Mobile Learning-Based Learning Media Using “Rumah Belajar” Application - Agus Setiawan; Muhyidin Thohir; Leli Fertiliana Dea; Ika Trisnawati Alawiyah; Asriatul Jannah (PT FORMOSA CENDEKIA GLOBAL, 2022)
Technological developments have a major impact on education so that educators must prepare themselves to develop the process and use of learning media as the main means of supporting learning. The purpose of this study is to train teachers to be able to use Rumah Belajars as a technology-based platform that can be used as a learning medium. This service method uses the Assed Based Communities Development (ABCD) approach with community service steps, namely discovery, dream, design, define, destiny. Assisted subjects are IPPNU members. The assisted result is that the assisted subjects of IPPNU members are able to use, design and utilize the Rumah Belajar platform so that it can be used as an alternative free learning media.